Risk Factors for Leprosy at Baingkete Makbon District Sorong Regency : - Jenni Lilis S Siagian; Sariana Pangaribuan; Atika S Ulimpa (Science Midwifery, 2022)
Indonesia is the third highest contributor to leprosy cases in the world. In 2018, 640 new cases were found in West Papua with a prevalence of 17.6 / 10,000, in Sorong Regency there were 350 cases. There are 22 lepers in Baingkete Village. It is known that the physical condition of the house does not meet the requirements, and the average elementary and junior high school education is thought to be a risk factor for leprosy. The research objective was to determine the risk factors for leprosy in Baingkete Village. This type of research is analytic observation, case control design. The research was conducted in Baingkete Village, Makbon District, Sorong Regency in November 2020. The population was all residents of Baingkete Village and a sample of 66 people consisted of 22 cases and 44 controls. The instruments used were questionnaires and observation sheets. Data analysis was performed using the odds ratio. The results showed that knowledge OR = 1.379, the physical condition of the house OR = 0.476, personal hygiene OR = 1.537. The conclusion is knowledge and personal hygiene are risk factors for leprosy while the physical condition of the house is a protective factor for leprosy. Suggestions for Makbon Health Center staff to work together with the community through visiting activities in an effort to prevent leprosy transmission from an early age. It is for the community to reduce the risk of transmission of leprosy through improving living behavior and environmental conditions as well as carrying out early detection.